The Impact Of Fundamentals And Technical Analysis On Stock Returns In Banking Companies Listed For Indonesia Stock Exchange 2013-2022 - Muhammad Rizki Alwi Ardana; Wisnu Panggah Setiyono; Sriyono Sriyono (UNIVED Press, 2024)
This study aims to provide understanding, knowledge, and testing of the Effect of Fundamental Factors Analysis and Technical Analysis on Stock Returns of Banking Companies listed on the Indonesia Stock Exchange for 2013-2022. The sampling technique used purposive sampling using the documentation model and data collection totaling 7 banking companies listed on the Stock Exchange and 70 total samples of banking companies in the 10-year time frame. The data analysis technique used in the data processing software is Eviews 12, using a linear regression model. The results of this study from the tests that have been carried out show that fundamental components such as price to sales ratio do not affect Stock Returns, Earnings per Share has an effect on Stock Returns, Cash Flow From Operation affects Stock Returns and technical components such as Trading Volume affects Stock Returns, and Market Capitalization does not affect Stock Returns.